Preparation method of hydrogen fuel cell catalyst and prepared catalyst
Through a new preparation method, the mixing treatment of crushed carbon black, polyvinylpyrrolidone and nitric acid solution and deionized water rinsing, combined with vacuum drying and reducing gas heat treatment, the problem of low activity and stability of existing platinum carbon catalysts was solved, and a high activity and stability catalyst was prepared, which promoted the commercialization of hydrogen fuel cells.
Patent Information
- Application Number
- CN202411983523.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing platinum carbon catalysts used in hydrogen fuel cells have low activity and stability due to the limitations of the preparation method, which hinders the commercial promotion of fuel cells.
A new hydrogen fuel cell catalyst preparation method is adopted, which includes mixing broken carbon black, polyvinylpyrrolidone and nitric acid solution with heat and reflux stirring, followed by rinsing with deionized water and drying under vacuum drying, and finally heat treatment in a reducing gas to prepare a platinum carbon catalyst with high activity and stability.
The catalyst prepared by this method has higher activity and stability, can effectively improve the performance of platinum carbon catalysts, and promote the commercial application of hydrogen fuel cells.
Smart Images

Figure CN119742383A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a battery catalyst, in particular to a method for preparing a hydrogen fuel cell catalyst and the prepared catalyst. Background Art
[0002] At present, most catalysts for hydrogen fuel cells on the market are platinum-carbon catalysts (Pt / C). The key physical properties of platinum-carbon catalysts (such as platinum particle size distribution, morphology, dispersion on the carrier, physical properties of carbon carriers and surface chemical properties, etc.) will seriously affect their activity and stability, and the key physical properties of platinum-carbon catalysts are closely related to their preparation methods. Existing common methods for preparing platinum-carbon catalysts include organic solvent thermal method, microemulsion method, colloid method, etc. These methods have high production costs, complex process control, impurities and / or surfactants that are difficult to remove, and involve the use of a large number of organic reagents. There are high difficulties in large-scale promotion. The platinum-carbon catalysts prepared by the existing methods have low activity and stability, which further hinders the commercial promotion and application of fuel cells. Therefore, how to ensure the controllability of the key physical properties of platinum-carbon catalysts to improve the activity and stability of platinum-carbon catalysts has become a problem of widespread concern. However, there is currently no corresponding technology and no relevant reports. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that the existing platinum-carbon catalyst used in hydrogen fuel cells is limited by the preparation method and has low activity and stability, and provides a method for preparing a hydrogen fuel cell catalyst, which has a simple production process, is easy to implement, has controllable product characteristics, and can improve the activity and stability of the prepared platinum-carbon catalyst. The present invention also discloses a catalyst prepared by the above-mentioned method for preparing a hydrogen fuel cell catalyst.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions:
[0005] A method for preparing a hydrogen fuel cell catalyst comprises the following steps:
[0006] Step S1, mixing crushed carbon black, polyvinyl pyrrolidone and a nitric acid solution with a concentration of 0.5 to 5M, heating to 60 to 120°C and reflux stirring for 3 to 12 hours, then rinsing the carbon black with deionized water until the filtrate after rinsing is neutral, then drying the rinsed carbon black at a drying temperature of 100 to 200°C under a vacuum environment for 6 to 12 hours to obtain pretreated conductive carbon black, and finally crushing the pretreated conductive carbon black to obtain a spare carbon carrier; wherein, when the carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed, the mass ratio of carbon black to polyvinyl pyrrolidone is 10 to 30:1, and the mass ratio of carbon black to nitric acid solution is 1:30 to 100;
[0007] Step S2, dissolving platinum precursor powder and an auxiliary agent in a mixed solution of deionized water and an organic liquid, stirring the mixture for 0.5 to 1 h at a temperature of 80 to 100° C. and an ultrasonic power of not less than 2 kW to obtain a platinum precursor solution; wherein the mass ratio of deionized water to the organic liquid is 1:1 to 20, the mass ratio of the platinum precursor powder to the mixed solution is 1:20 to 200, and the mass ratio of the auxiliary agent to the mixed solution is 1:100-500;
[0008] Step S3, placing the spare carbon carrier in the barrel, closing the barrel and evacuating the barrel so that the vacuum degree in the barrel is maintained at no more than 200pa, spraying the platinum precursor solution into the barrel, maintaining the barrel at a constant temperature of 20-25°C during the spraying period and continuously dispersing and stirring the material in the barrel, with a dispersion rate of 500-2000rpm and a dispersion stirring time of 10-60min; after the dispersion stirring, stop evacuating the barrel, and introduce nitrogen into the barrel to pressurize the material, with a pressurization pressure of 0.1-0.5MPa and a pressurization time of 5-20min; After the pressure treatment is completed, the barrel is evacuated again to keep the vacuum degree in the barrel not higher than 200 Pa and the barrel is kept at a constant temperature of 100° C. to evaporate the solvent for 1 to 2 hours; wherein, the mass ratio of platinum in the platinum precursor solution to the mass of the spare carbon carrier is 1:0.5 to 4, the platinum precursor solution is divided into no less than three parts, and one portion of the platinum precursor solution is sprayed during each spraying period. After the above-mentioned dispersion stirring, pressure treatment and solvent evaporation steps are completed, another portion of the platinum precursor solution is sprayed, and the above steps are repeated until all the platinum precursor solutions are sprayed to obtain the sample;
[0009] Step S4, quenching the sample obtained in step S3 with liquid nitrogen and placing it in a freeze dryer for freeze drying for 8 to 24 hours to obtain a freeze-dried powder;
[0010] Step S5, heat-treating the freeze-dried powder in a reducing mixed gas at a temperature of 400-900° C. for 1-3 hours to obtain a catalyst; wherein the reducing mixed gas includes 5-10 Vol% of reducing gas ammonia, and the rest is argon or nitrogen.
[0011] In step S1 of the present invention, the crushed carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed, and refluxed and stirred under heating. After the treatment is completed, the excess nitric acid is rinsed and removed with deionized water until the filtrate is neutral after rinsing, and then the carbon black filter cake is vacuum dried. During the vacuum drying, a vacuum pump is used to maintain a vacuum environment and the vacuum pump is continuously operated to obtain a pre-treated conductive carbon black. Finally, the pre-treated conductive carbon black is crushed with a crusher to obtain a spare carbon carrier. Step S1 of the present invention is a carbon carrier pretreatment step. The purpose of the carbon carrier pretreatment is to introduce uniformly distributed oxygen-containing groups such as carboxyl and phenolic hydroxyl groups in a controllable amount (the carbon black surface will form oxygen-containing groups such as carboxyl and phenolic hydroxyl groups under the oxidation of nitric acid), so as to facilitate the substitution reaction of the nitrogen source with the carboxyl and phenolic hydroxyl groups in the later step S5 to realize the nitrogen functionalization of the carbon carrier; in addition, the oxygen-containing groups can be used as platinum salt adsorption and precipitation sites, which is conducive to promoting the uniform distribution of platinum salts on the surface of the carbon carrier. In the step S1 of the present invention, the carbon carrier pretreatment stage adopts nitric acid treatment. The nitric acid treatment will increase the number of surface defects of the carbon material and even destroy the structure. Polyvinyl pyrrolidone can be used as a dispersant for the carbon material in the solution, which helps the carbon carrier to obtain uniform oxidation treatment. The polyvinyl pyrrolidone adsorbed on the surface of the carbon material can be used as a carbon material defect repair agent in the subsequent heat treatment process, reducing the corrosion-prone sites on the surface of the carbon material, effectively improving the service life of the carbon carrier, thereby enhancing the service life of the catalyst.
[0012] In step S2 of the present invention, platinum precursor powder and auxiliary agent are dissolved in a mixed solution of deionized water and organic liquid in a glass kettle. The auxiliary agent mainly improves the stability and dispersibility of the platinum salt in the solution, adjusts the fluidity of the platinum salt on the surface of the carbon carrier, and promotes the uniform coverage of the platinum salt on the surface of the carbon carrier. The proportion of deionized water and organic liquid is mainly to adjust the solubility of the platinum salt in the mixed solution, so that the platinum salt is in a nearly saturated state, which is convenient for the subsequent solution evaporation process. The platinum salt can quickly precipitate and form a growth site for platinum nanoparticles. When step S2 of the present invention is implemented, the greater the ultrasonic power, the better the dispersion effect; the value of 2KW is to ensure that there is enough ultrasonic power to ensure a sufficient ultrasonic dispersion effect.
[0013] The material direction adopted in step S3 of the present invention is a double-layered barrel of a double planetary mixer. The vacuum environment of the barrel is maintained by a vacuum pump. The platinum precursor solution is sprayed into the barrel through a spray head. During the spraying of the platinum precursor solution, the dispersion system and the stirring system of the double planetary mixer are turned on to continuously disperse and stir the material, and the circulating refrigerator is turned on to cool the barrel so that the barrel is in a constant temperature state; after dispersion and stirring, the vacuum pump and the valve are closed, and the nitrogen valve is opened to introduce nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on to evaporate the solvent. During the evaporation of the solvent, the circulating refrigerator valve is first closed, and the circulating heater is turned on to heat the barrel at a constant temperature of 100°C. In step S3 of the present invention, the multiple spraying-vacuum-stirring / dispersing-nitrogen pressurization treatment of the platinum salt precursor solution is to force the platinum salt to be mixed with the carbon carrier as evenly as possible and to be immersed in the pores of the carbon carrier; wherein, the vacuum-nitrogen pressurization treatment process can clean and replace the oxygen, solvent, etc. inside the pores of the carbon carrier, thereby preventing the platinum nanoparticles generated in the subsequent thermal reduction process from being oxidized, resulting in an increase in the content of oxidized platinum. Vacuuming can lower the boiling point of the solvent and assist in solvent evaporation. In step S3 of the present invention, when the barrel is kept at a constant temperature of 100°C for solvent evaporation, the solvent is evaporated for 1 to 2 hours until the solvent is evaporated to a point where it is no longer visible to the naked eye, and then the heating is stopped.
[0014] The freeze drying in step S4 of the present invention is characterized by in-situ freeze drying of the material, and the dried material can maintain its original chemical composition and physical properties, avoiding the decomposition of platinum salts caused by other heating-type drying; secondly, the freeze-dried material is in a fluffy powder state, and the fluffy powder is conducive to sufficient contact reaction with the reaction gas in the subsequent thermal reduction process, which is conducive to improving the consistency of the catalyst product. In step S4 of the present invention, the sample is placed in a freeze dryer for freeze drying. The high vacuum environment (<10Pa) of the freeze dryer can promote the discharge of oxygen and solvent inside the pores of the carbon carrier, prevent the platinum nanoparticles generated in the subsequent thermal reduction process from being oxidized, and lead to an increase in the content of oxidized platinum.
[0015] In the specific implementation of step S5 of the present invention, the freeze-dried powder is placed in a rotary tube furnace. The main purpose of using a rotary tube furnace is to reduce the heterogeneity of the material being heated. At the same time, the rotation of the furnace tube drives the material to turn over, which is conducive to the full contact reaction between the material and the reaction gas, and can improve the consistency of the catalyst product. Step S5 of the present invention is heat-treated in an atmosphere containing ammonia, firstly to reduce the platinum salt to elemental platinum; secondly, to ensure that the oxygen-containing functional groups on the surface of the formed catalyst are as few as possible, thereby increasing the zero-valent platinum content in the catalyst; thirdly, ammonia can react with the oxygen-containing groups on the surface of the carbon carrier to achieve the grafting of nitrogen-containing groups on the surface of the carbon carrier.
[0016] Furthermore, in step S1, the carbon black added when the carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed has a specific surface area of 400 to 1200 m 2 / g, the added carbon black is mechanically crushed and passed through a 400-mesh sieve, and the graphite crystallite size of the carbon black is 2 to 5 nm. In step S1 of the present invention, when the crushed carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed, if the specific surface area of the carbon black is less than 400 m 2 / g, which is not conducive to the dispersion and loading of platinum particles; if the specific surface area of carbon black is higher than 1200m 2 / g, the stability of carbon black will deteriorate. The present invention limits the specific surface area of carbon black to 400-1200m 2 / g, while ensuring the stability of carbon black, it is also convenient for the dispersion and loading of platinum particles. Graphite crystallites are the part of graphite crystallization on the surface / inside of carbon black. The larger the crystallite size, the better the surface carbon black stability. However, the crystallite size should not be too high. Too high a crystallite size indicates that the degree of graphitization of carbon black is too high, which will be unfavorable for the loading and dispersion of platinum particles. The present invention limits the graphite crystallite size to 2-5nm, which further ensures the stability of carbon black and is conducive to the dispersion and loading of platinum particles. The advantage of the screening of the present invention is to avoid larger carbon black agglomerated particles, and the crushed carbon black can have a larger contact surface with the nitric acid solution, thereby obtaining sufficient surface oxidation treatment.
[0017] Furthermore, the molecular weight of the polyvinyl pyrrolidone is not higher than 40000. High molecular weight polyvinyl pyrrolidone is too viscous and is not conducive to the dispersion of the carbon carrier. The present invention limits the molecular weight of polyvinyl pyrrolidone to no more than 40000, that is, using low molecular weight polyvinyl pyrrolidone is more conducive to the dispersion of the carbon carrier.
[0018] Furthermore, the platinum precursor powder is any one of tetraamineplatinum dibicarbonate, tetraamineplatinum oxalate, tetraamineplatinum hydrogen phosphate, tetraamineplatinum acetate, tetraamineplatinum sulfate, tetraamineplatinum nitrate, dinitrosodiammineplatinum, tetraamineplatinum dichloride, ammonium chloroplatinate, and tetraamineplatinum dihydroxide, or a combination of two or more thereof.
[0019] Furthermore, the auxiliary agent is any one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acyl alkanolamine polyoxyethylene ether and octylphenol polyoxyethylene ether.
[0020] Furthermore, the organic liquid is any one of isopropanol, n-propanol, glycerol, acetic acid, and trichloroacetaldehyde, or a combination of two or more thereof.
[0021] A hydrogen fuel cell catalyst is prepared by the above-mentioned method for preparing a hydrogen fuel cell catalyst.
[0022] In summary, the present invention has the following beneficial effects compared with the prior art: the present invention aims at the disadvantages of strongly adsorbed chloride ions, difficult-to-remove organic matter, poor size distribution of platinum nanoparticles (platinum nanoparticles are too large or too small, which easily leads to low catalyst activity or poor stability), poor dispersion of platinum nanoparticles (there are a large number of platinum particle agglomerates, which easily lead to low platinum utilization and poor activity), and undesirable location of platinum nanoparticles (such as mainly existing on the surface of carbon carriers, which are easily poisoned by ionomers, resulting in low catalyst activity, and platinum nanoparticles are easily dissolved, migrated, agglomerated, and detached during actual operation, which leads to a significant decrease in catalyst performance). By improving the process steps and material usage, the stability of the platinum precursor solution and the impregnation efficiency and effect in the porous carbon carrier can be improved, and the compatibility of the carbon carrier can be improved, so that the physicochemical properties of the catalyst can be effectively regulated (such as the particle size distribution of platinum nanoparticles, the location and proportion of platinum nanoparticles, the nitrogen content and distribution, and the number of surface defects of carbon materials). Thus, the present invention can improve the shortcomings of low utilization rate of active components, poor stability and poor ionomer distribution of platinum-carbon catalysts prepared by existing processes, while also avoiding the negative corrosion effects of oxidative solutions on carbon carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0024] Figure 1 TEM image of the catalyst of Example 1;
[0025] Figure 2 TEM image of the catalyst of Comparative Example 1;
[0026] Figure 3 TEM image of the catalyst of Comparative Example 2;
[0027] Figure 4 TEM image of the catalyst of Comparative Example 3;
[0028] Figure 5 The fresh membrane electrode IV test curves of the catalysts of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0029] Figure 6 The IV test curves of the catalysts of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 after membrane electrode cycling;
[0030] Figure 7 The IV test curves of the catalysts of Example 1 and Comparative Example 4 before and after membrane electrode cycle;
[0031] Figure 8TEM image of the membrane electrode of the catalyst of Example 1 after cycling;
[0032] Fig. 9 TEM image of the membrane electrode of the catalyst of Comparative Example 2 after cycling;
[0033] Fig.10 TEM image of the membrane electrode of the catalyst of Comparative Example 3 after cycling;
[0034] Fig.11 The XRD test patterns of the catalysts of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown;
[0035] Fig.12 The XRD test patterns of the catalyst layers after membrane electrode cycles of the catalysts of Example 1, Comparative Example 2 and Comparative Example 3;
[0036] Fig.13 It is a test chart of nitrogen content of the catalysts of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0037] Fig.14 This is a graph showing the corrosion sensitivity of the carbon support in comparative example 5. DETAILED DESCRIPTION
[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0039] Embodiment 1:
[0040] Take Japanese Lion Ketjen Black EC300J superconducting carbon black (KB300 for short) and crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 0.5g of polyvinyl pyrrolidone and 600g of 2M nitric acid solution, mix and stir, and reflux and stir at 80°C for 8 hours. After the reflux is completed, rinse the carbon black with deionized water until the filtrate after rinsing is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after the carbon black sample is vacuum dried, it is crushed by a crusher to be a standby carbon carrier. Among them, the specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, the graphite crystallite size of carbon black is 2-5nm, and the molecular weight of polyvinyl pyrrolidone is 10000.
[0041] Take 15.63g of tetraamine platinum acetate, 1305g of a mixed solution (the mixed solution contains 305g of deionized water and 1000g of acetic acid), and 3.26g of alkylphenol polyoxyethylene ether and put them into a glass kettle. At the same time, the materials are assisted with stirring and ultrasound. The stirring and ultrasound time is 60 minutes, the ultrasonic power is 3KW, and the temperature of the mixed material is 90°C.
[0042] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum acetate solution is sprayed into the barrel through the spray head; during the spraying of the tetraamine platinum acetate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the vacuum pump and valve are closed, and the nitrogen valve is opened to pass nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on for solvent evaporation, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the tetraamine platinum acetate solution is divided into three parts, and a platinum precursor solution is sprayed during each spraying. After the above-mentioned dispersion stirring, pressurization treatment and solvent evaporation steps are completed, another platinum precursor solution is sprayed, and the above steps are repeated until all three platinum precursor solutions are sprayed to obtain a sample. During the dispersion and stirring, the circulating refrigerator is turned on to cool the barrel to keep the barrel in a constant temperature state. The barrel constant temperature is 20°C, the dispersion and stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the evaporation of the solvent, first close the circulating refrigeration machine valve, and at the same time turn on the circulating heating machine to heat the barrel at a constant temperature of 100°C for 1 hour; when evacuating, the vacuum degree is 80pa; the pressurization pressure is 0.5MPa, and the pressurization time is 10 minutes.
[0043] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying to obtain freeze-dried powder, and the freeze drying time was 12 hours;
[0044] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled PtC-1, with a platinum loading of 50 wt%.
[0045] Embodiment 2:
[0046] Take Japanese Lion Ketjen Black EC300J superconducting carbon black (KB300 for short) and crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 1g of polyvinyl pyrrolidone and 1000g of 2M nitric acid solution, mix and stir, and reflux at 100°C for 6 hours. After the reflux is completed, rinse the carbon black until the filtrate is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after the carbon black sample is vacuum dried, it is crushed by a crusher to be a standby carbon carrier. Among them, the specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, the graphite crystallite size of carbon black is 2-5nm, and the molecular weight of polyvinyl pyrrolidone is not higher than 8000.
[0047] 15.63g of tetraammine platinum acetate, 2000g of mixed solution (800g of water and 1200g of isopropanol), and 5g of octylphenol polyoxyethylene ether were put into a glass kettle, and the materials were stirred and ultrasonicated for 30 minutes, with an ultrasonic power of 3KW and a mixed material temperature of 90°C;
[0048] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum acetate solution is sprayed into the barrel through the spray head; during the spraying of the tetraamine platinum acetate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the vacuum pump and valve are closed, and the nitrogen valve is opened to pass nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on for solvent evaporation, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the tetraamine platinum acetate solution is divided into four parts, and a platinum precursor solution is sprayed during each spraying. After the above-mentioned dispersion stirring, pressurization treatment and solvent evaporation steps are completed, another platinum precursor solution is sprayed, and the above steps are repeated until all four platinum precursor solutions are sprayed to obtain a sample. During the dispersion and stirring, the circulating refrigerator is turned on to cool the barrel so that the barrel is in a constant temperature state. The constant temperature of the barrel is 20°C, the dispersion and stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the evaporation of the solvent, the circulating refrigeration machine valve is closed first, and the circulating heating machine is turned on at the same time to heat the barrel at a constant temperature of 100°C for 2 hours; when evacuating, the vacuum degree is 40pa; the pressurization pressure is 0.2MPa, and the pressurization time is 20 minutes;
[0049] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying; the freeze drying time was 16 hours;
[0050] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 800°C for 1 hour at a heating rate of 5°C / min; the reducing mixed gas included 10 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled Pt / C-2, with a platinum loading of 50wt%.
[0051] Embodiment 3:
[0052] Take Japanese Lion Ketjen Black EC300J superconducting carbon black (KB300 for short) and crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 0.4g of polyvinyl pyrrolidone and 800g of 2M nitric acid solution, mix and stir, and reflux at 60°C for 12 hours. After the reflux is completed, rinse the carbon black until the filtrate is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after the carbon black sample is vacuum dried, it is crushed by a crusher to be a standby carbon carrier. Among them, the specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, the graphite crystallite size of carbon black is 2-5nm, and the molecular weight of polyvinyl pyrrolidone is 10000.
[0053] 15.63g of tetraammine platinum acetate, 1000g of mixed solution (500g of water, 500g of n-propanol), and 3.5g of fatty alcohol polyoxyethylene ether were put into a glass kettle, and the materials were assisted with stirring and ultrasound. The stirring and ultrasound time was 60 minutes, the ultrasonic power was 3KW, and the temperature of the mixed material was 90°C;
[0054] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum acetate solution is sprayed into the barrel through the spray head; during the spraying of the tetraamine platinum acetate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the vacuum pump and valve are closed, and the nitrogen valve is opened to pass nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on for solvent evaporation, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the tetraamine platinum acetate solution is divided into three parts, and a platinum precursor solution is sprayed during each spraying. After the above-mentioned dispersion stirring, pressurization treatment and solvent evaporation steps are completed, another platinum precursor solution is sprayed, and the above steps are repeated until all three platinum precursor solutions are sprayed to obtain a sample. During the dispersion and stirring, the circulating refrigerator is turned on to cool the barrel to keep the barrel in a constant temperature state. The barrel constant temperature is 20°C, the dispersion and stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the evaporation of the solvent, the circulating refrigeration machine valve is closed first, and the circulating heating machine is turned on at the same time to heat the barrel at a constant temperature of 100°C for 1 hour; when evacuating, the vacuum degree is 200pa; the pressurization pressure is 0.5MPa, and the pressurization time is 20 minutes;
[0055] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying; the freeze drying time was 24 hours;
[0056] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 400°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled Pt / C-3, with a platinum loading of 50 wt%.
[0057] Embodiment 4:
[0058] Take Japanese Lion Ketjen Black EC300J superconducting carbon black (KB300 for short) and crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 0.8g of polyvinyl pyrrolidone and 600g of 2M nitric acid solution, mix and stir, and reflux at 80°C for 12 hours. After the reflux is completed, rinse the carbon black until the filtrate is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after the carbon black sample is vacuum dried, it is crushed by a crusher to be a standby carbon carrier. Among them, the specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, the graphite crystallite size of carbon black is 2-5nm, and the molecular weight of polyvinyl pyrrolidone is 24000.
[0059] 14.41 g of tetraammine platinum oxalate, 1000 g of a mixed solution (500 g of water and 500 g of isopropanol), and 3.3 g of fatty acyl alkanolamine polyoxyethylene ether were put into a glass kettle, and the materials were stirred and ultrasonicated for 45 minutes, with an ultrasonic power of 3 KW, and the temperature of the mixed material was 90 ° C.
[0060] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum oxalate solution is sprayed into the barrel through the spray head; during the spraying of the tetraamine platinum oxalate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the vacuum pump and valve are closed, and the nitrogen valve is opened to pass nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on for solvent evaporation, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the mass ratio of platinum to the mass of the spare carbon carrier in the tetraamine platinum oxalate solution is 1:1, and the tetraamine platinum oxalate solution is divided into five parts. During each spraying, a portion of the platinum precursor solution is sprayed. After the above-mentioned dispersion and stirring, pressurization treatment and solvent evaporation steps are completed, another portion of the platinum precursor solution is sprayed, and the above steps are repeated until all five portions of the platinum precursor solution are sprayed to obtain a sample. During the dispersion and stirring period, the circulating refrigerator is turned on to cool the barrel to keep the barrel in a constant temperature state. The barrel constant temperature is 20°C, the dispersion and stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the solvent evaporation period, the circulating refrigerator valve is closed first, and the circulating heater is turned on to heat the barrel at a constant temperature of 100°C for 1 hour; when evacuating, the vacuum degree is 100pa; the pressurization pressure is 0.4MPa, and the pressurization time is 15 minutes;
[0061] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying; the freeze drying time was 24 hours;
[0062] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 700°C for 1 hour at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled Pt / C-4, with a platinum loading of 50wt%.
[0063] Comparative Example 1:
[0064] Take Japanese Lion KB300 superconducting carbon black, crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 0.5g of polyvinyl pyrrolidone and 600g of 2M nitric acid solution, mix and stir, and reflux and stir at 80°C for 8 hours. After reflux and stirring, rinse the carbon black with deionized water until the filtrate after rinsing is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after vacuum drying, crush the carbon black sample with a crusher to obtain a spare carbon carrier. The specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, polyvinyl pyrrolidone molecular weight 10000.
[0065] 15.63g of tetraamine platinum acetate, 1305g of a mixed solution (the mixed solution contains 305g of deionized water and 1000g of acetic acid) and 3.26g of alkylphenol polyoxyethylene ether are put into a glass kettle, and the materials are stirred and ultrasonicated for 60 minutes, with an ultrasonic power of 3KW and a mixed material temperature of 90°C.
[0066] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, turn on the vacuum pump for vacuuming; tetraamine platinum acetate solution is sprayed into the barrel through the spray head; after spraying the tetraamine platinum acetate solution, close the vacuum pump and valve, and open the nitrogen valve to pass nitrogen to pressurize the material; after the pressurization treatment is completed, turn on the vacuum pump for solvent evaporation, and keep the barrel at a constant temperature of 100°C. In this embodiment, the mass ratio of platinum in the tetraamine platinum acetate solution to the mass of the spare carbon carrier is 1:1, and the above-mentioned process of spraying the tetraamine platinum acetate solution is completed at one time. During the spraying period, turn on the circulating refrigeration machine to cool the barrel so that the barrel is in a constant temperature state, and the constant temperature of the barrel is 20°C. During the evaporation of the solvent, first close the circulating refrigeration machine valve, and at the same time turn on the circulating heating machine to heat the barrel at a constant temperature of 100°C for 1 hour; when vacuuming, the vacuum degree is 80pa; the pressurization pressure is 0.5MPa, and the pressurization time is 10 minutes;
[0067] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying to obtain freeze-dried powder, and the freeze drying time was 12 hours;
[0068] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled PtC-5, with a platinum loading of 50wt%.
[0069] Comparative Example 2:
[0070] Take Japanese Lion KB300 superconducting carbon black, crush it mechanically and pass it through a 400-mesh sieve for later use; weigh 10g of crushed carbon black, 0.5g of polyvinyl pyrrolidone and 600g of 2M nitric acid solution, mix and stir, and reflux and stir at 80°C for 8 hours. After reflux and stirring, rinse the carbon black with deionized water until the filtrate after rinsing is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after vacuum drying, crush the carbon black sample with a crusher to obtain a spare carbon carrier. The specific surface area of the carbon black used in the mixing and stirring is 800m 2 / g, polyvinyl pyrrolidone molecular weight 10000.
[0071] Take 15.63g of tetraamine platinum acetate and 1305g of a mixed solution (the mixed solution contains 305g of deionized water and 1000g of acetic acid), and stir and ultrasonicate the materials for 60 minutes, with an ultrasonic power of 3KW and a mixed material temperature of 90°C.
[0072] 8g of crushed carbon carrier is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum acetate solution is sprayed into the barrel through the spray head; during the spraying of the tetraamine platinum acetate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the valve is closed, and the vacuum pump is turned on at the same time to evaporate the solvent, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the mass ratio of platinum to the mass of the spare carbon carrier in the tetraamine platinum acetate solution is 1:1, and the tetraamine platinum acetate solution is divided into three parts. During each spraying, a portion of the platinum precursor solution is sprayed. After the above-mentioned dispersion stirring, pressure treatment and solvent evaporation steps are completed, another portion of the platinum precursor solution is sprayed, and the above steps are repeated until all three portions of the platinum precursor solution are sprayed to obtain a sample. During the dispersion stirring, the circulating refrigerator is turned on to cool the barrel to keep the barrel in a constant temperature state. The constant temperature of the barrel is 20°C, the dispersion stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the evaporation of the solvent, the circulating refrigeration machine valve is closed first, and the circulating heating machine is turned on at the same time to heat the barrel at a constant temperature of 100°C for 1 hour; when evacuating, the vacuum degree is 80pa;
[0073] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying to obtain freeze-dried powder, and the freeze drying time was 12 hours;
[0074] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled PtC-6, with a platinum loading of 50wt%.
[0075] Comparative Example 3:
[0076] Take Japanese Lion KB300 superconducting carbon black and 0.5g polyvinyl pyrrolidone, mix them through mechanical crushing and pass through a 400-mesh sieve for later use. The specific surface area of the carbon black used in the mixing is 800m 2 / g, polyvinyl pyrrolidone molecular weight 10000.
[0077] Take 15.63g of tetraamine platinum acetate, 1305g of a mixed solution (the mixed solution contains 305g of deionized water and 1000g of acetic acid), and 3.26g of alkylphenol polyoxyethylene ether and put them into a glass kettle. At the same time, the materials are assisted with stirring and ultrasound. The stirring and ultrasound time is 60 minutes, the ultrasonic power is 3KW, and the temperature of the mixed material is 90°C.
[0078] 8g of crushed carbon black is placed in the double-layer barrel of the double planetary mixer. After closing the barrel, the vacuum pump is turned on for vacuuming; the tetraamine platinum acetate solution is sprayed into the barrel through a spray head; during the spraying of the tetraamine platinum acetate solution, the dispersion system and stirring system of the double planetary mixer are turned on to continuously disperse and stir the material; after dispersion and stirring, the vacuum pump and valve are closed, and the nitrogen valve is opened to introduce nitrogen to pressurize the material; after the pressurization treatment is completed, the vacuum pump is turned on for solvent evaporation, and the barrel is kept at a constant temperature of 100°C. In this embodiment, the mass ratio of platinum to the mass of the spare carbon carrier in the tetraamine platinum acetate solution is 1:1, and the tetraamine platinum acetate solution is divided into three parts. During each spraying, a portion of the platinum precursor solution is sprayed. After the above-mentioned dispersion and stirring, pressurization treatment and solvent evaporation steps are completed, another portion of the platinum precursor solution is sprayed, and the above steps are repeated until all three portions of the platinum precursor solution are sprayed to obtain a sample. During the dispersion and stirring period, the circulating refrigerator is turned on to cool the barrel to keep the barrel in a constant temperature state. The barrel constant temperature is 20°C, the dispersion and stirring time is 60 minutes, and the dispersion rate is 1000rpm. During the solvent evaporation period, the circulating refrigerator valve is closed first, and the circulating heater is turned on to heat the barrel at a constant temperature of 100°C for 1 hour; when evacuating, the vacuum degree is 80pa; the pressurization pressure is 0.5MPa, and the pressurization time is 10 minutes;
[0079] The sample was rapidly cooled with liquid nitrogen and placed in a freeze dryer for freeze drying to obtain freeze-dried powder, and the freeze drying time was 12 hours;
[0080] The freeze-dried powder was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% hydrogen and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled PtC-7, with a platinum loading of 50wt%.
[0081] Comparative Example 4:
[0082] The catalyst was synthesized by microwave-assisted ethylene glycol synthesis, and the carbon carrier was Lion KB300 superconducting carbon black from Japan. 500 mL of chloroplatinic acid ethylene glycol solution with a platinum concentration of 1 mg / mL was poured into a 1L glass reactor and stirred for 10 minutes, then 30 mL of 1M sodium hydroxide ethylene glycol solution was added and stirred for 10 minutes, then 100 mL of KB300 superconducting carbon black / ethylene glycol suspension with a carbon carrier concentration of 5 mg / mL was added and mixed and stirred for 10 minutes, then the glass reactor was placed in a microwave reaction device and reacted at 160°C for 5 minutes. After the reaction was completed, the slurry was cooled to room temperature, and then a 0.2M hydrochloric acid solution was added to the slurry to adjust the pH of the slurry to 2 to accelerate the precipitation of the catalyst. Finally, the catalyst was filtered out and washed with boiling water at 90-100°C. The filtrate was neutral, and the washed catalyst was dried at 70°C in a vacuum for 12 hours. The dried catalyst was placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas included 5 Vol% ammonia and the rest was argon. After the heat treatment, the desired catalyst was obtained, labeled PtC-8, with a platinum loading of 50 wt%.
[0083] Comparative Example 5:
[0084] Take Japanese Lion KB300 superconducting carbon black, crush it mechanically and pass it through a 400-mesh sieve for standby use; weigh 10g of the crushed carbon black, 0.5g of polyvinyl pyrrolidone (molecular weight 10000) and 600g of 2M nitric acid solution, mix and stir, and reflux at 80°C for 8 hours. After the reflux is completed, rinse the carbon black until the filtrate is neutral; place the rinsed carbon black sample in a vacuum drying oven and vacuum dry it at 120°C for 8 hours; after the carbon black sample is vacuum dried, it is crushed by a crusher to obtain a standby carbon carrier, and the standby carbon carrier is marked as O-KB300;
[0085] The spare carbon carrier powder O-KB300 is placed in a rotary tube furnace and heat treated in a reducing mixed gas at a temperature of 600°C for 2 hours at a heating rate of 5°C / min; the reducing mixed gas includes 5 Vol% ammonia and the rest is argon. After the heat treatment is completed, the desired carbon carrier is obtained, which is marked as N-KB300.
[0086] Test example:
[0087] TEM test: first scrape off the catalyst on the cathode side of the membrane electrode after the cycle with a blade; then take an appropriate amount of the scraped sample and add it to a centrifuge tube with ethanol and water (volume ratio 1:1), and shake it evenly with ultrasound; drop an appropriate amount of the mixed liquid on the copper mesh, dry it, and then put it into the transmission electron microscope for testing.
[0088] XRD test: Cut the catalyst layer before and after the cycle into strips of 20mm wide and 35mm long with a blade, fix them flatly on the sample slot with the cathode side facing up with tape, and then put the sample slot into the XRD tester for testing to obtain the XRD spectrum of the catalyst layer; the test scan rate is 5° / min, and the scanning angle range is 20-80°; finally, calculate the average particle size of the platinum nanoparticles according to the Scherrer formula.
[0089] Membrane electrode test: Weigh the prepared platinum-carbon catalyst powder, add a certain proportion of pure water, isopropanol and Nafion solution in turn, mix, and ultrasonically homogenize the mixture to obtain a catalyst slurry for use. Among them, the mass ratio of each component is as follows: Nafion to carbon mass ratio 0.7, isopropanol: pure water = 1:1, platinum-carbon catalyst: (mixed solution of isopropanol and pure water) = 1:20. Load the slurry into the ultrasonic spraying device and spray it on both sides of the proton exchange membrane, respectively, with a platinum loading of 0.05 mg / cm on the anode surface. 2 , cathode platinum loading 0.3mg / cm 2 , and dried at 80℃, and hot pressed on a hot press to form a membrane electrode with carbon paper and frame. The prepared membrane electrode is loaded into the test fixture, and then the fixture is connected to the fuel cell test bench for testing. The battery temperature is 80℃, the relative humidity of the anode is 50%, the relative humidity of the cathode is 30%, the back pressure of the cathode and cathode is 150Kps, and the gas stoichiometric ratio of the cathode and cathode is 1.8.
[0090] Carbon carrier corrosion sensitivity test: 10 mg carbon carrier, 2.5 mL water, and 2.5 mL isopropanol were placed in a 10 mL glass bottle and ultrasonically mixed for ten minutes; then 100 μL nafion solution (D520) was added and ultrasonicated for ten minutes. The ultrasonication process was carried out in an ice water bath. The mixed slurry was dripped onto the disk electrode, and the carbon carrier drop loading was 40 μg / cm 2 After the droplets are dried, the corrosion sensitivity test of the carbon carrier is carried out. The test steps are as follows: ①CV test voltage range 0.05-1.0V, scan rate 10mV / s; ②0.8V constant voltage 10s, 1.4V constant voltage 50s, cycle this step 10 times; ③CV test voltage range 0.05-1.0V, scan rate 10mV / s; the test system is 0.1M nitrogen saturated perchloric acid solution, and the test temperature is 25°C. The ratio of the integral area of the CV curve of step ③ to step ① is the value that characterizes the corrosion sensitivity of the carbon carrier.
[0091] Table 1 Comparison of voltage values at different current densities in the membrane electrode test data of catalyst samples
[0092]
[0093] like Figures 1 to 14As can be seen from the data in Table 1, the test results of Example 1 show that the process of the present invention has good feasibility and can prepare Pt / C catalysts with excellent electrochemical performance. Comparative Example 1 is compared with Example 1. The preparation process changes the number of spraying of the platinum precursor solution and does not involve the opening of the dispersion / stirring system. Comparative Example 2 is compared with Example 1. The preparation process does not involve the amount of additives added and nitrogen pressurization treatment. From the TEM test results (such as Figure 1 , 2 , 3), it can be seen that the reduction in the number of spraying times of the platinum precursor solution and the operation without a dispersion / stirring system will lead to the growth of platinum nanoparticles and uneven size distribution, resulting in a decrease in the initial activity of the catalyst (as shown in Figure 5 , as shown in Table 1), this is because spraying the platinum precursor solution in small amounts multiple times is to allow more platinum salts to penetrate into the pores of the carbon carrier. The opening of the dispersion / stirring system is to promote the uniform mixing of materials during the impregnation of the platinum precursor solution into the carbon carrier, to avoid the majority of the platinum salts from being concentratedly adsorbed on the surface of the carbon carrier or in the pores of the carbon carrier accumulation body, thereby preventing the agglomeration to form larger particles during the subsequent thermal reduction process. The presence of additives can improve the stability and dispersibility of the platinum salt in the solution, and improve the fluidity of the platinum salt precursor, so that the platinum salt can be quickly and evenly coated on the surface of the carbon carrier; nitrogen pressure treatment can further promote the penetration of the platinum salt precursor solution into the pores of the carbon carrier. When the additives and nitrogen pressure treatment are missing, it will cause the platinum precursor solution to be difficult to evenly cover the surface of the carbon carrier and to penetrate into the pores of the carbon carrier, resulting in a significant disadvantage in the dispersion and size control of the platinum nanoparticles. The platinum nanoparticles are also more likely to dissolve, migrate, agglomerate, and fall off during the electrochemical cycle (such as Fig. 9 shown).
[0094] Comparative Example 4 adopts the traditional ethylene glycol liquid phase reduction method. In this process, the platinum precursor cannot penetrate into the pores of the carbon support in large quantities, resulting in most of the platinum nanoparticles existing on the surface of the carbon support. The platinum nanoparticles on the surface of the carbon support are in direct contact with the ionomer and are severely poisoned, resulting in low catalyst activity; since most of the platinum nanoparticles exist on the surface of the carbon support, the platinum nanoparticles are more likely to dissolve, migrate, agglomerate, and fall off, thereby significantly reducing the catalyst stability (such as Figure 7 , as shown in Table 1).
[0095] Compared with Example 1, Comparative Example 3 lacks the pretreatment process of the carbon carrier and the reducing gas does not contain a nitrogen source. The pretreatment process can evenly introduce oxygen-containing groups on the surface of the carbon carrier. From the TEM image of Example 1, it can be seen that the catalyst sample has almost no agglomerated platinum nanoparticles and the platinum nanoparticles are evenly dispersed. It can be seen that the oxygen-containing groups can be used as adsorption and precipitation sites for platinum salts, which is beneficial to promote the uniform distribution of platinum salts on the surface of the carbon carrier, and obtain platinum nanoparticles with smaller particle size and more uniform dispersion (such as Figure 1 , 4, 11). In addition, the oxygen-containing groups can react with the nitrogen source in the gas and the nitrogen source thermally decomposed from the platinum salt precursor during the subsequent heat treatment process to convert the oxygen-containing groups (such as -OH, -COOH) into nitrogen-containing groups (such as -NH2, -CONH2) (such as Fig.13 As shown in the figure, the nitrogen-containing groups and platinum nanoparticles interact strongly, and the platinum nanoparticles are firmly anchored on the surface of the carbon carrier, which can slow down the dissolution, migration, agglomeration, and shedding of the platinum nanoparticles during the electrochemical cycle, thereby enhancing the stability of the catalyst system (as shown in the figure). Figure 8 , 10 , 12, as shown in Table 1); the presence of nitrogen-containing groups can improve the electronic structure of adjacent active components and enhance the catalytic activity of the catalyst system; in addition, the nitrogen-containing groups are positively charged, and through the interaction between charges, they can promote the uniform coverage of the surface negatively charged ionomers on the surface of the nitrogen-functionalized carbon carrier, thereby greatly reducing the local oxygen mass transfer resistance. In summary, the introduction of nitrogen-containing groups on the carbon carrier can improve the interaction relationship between the carbon carrier-platinum nanoparticles-ionomers, thereby achieving high activity and high stability of the catalyst (such as Figure 5 , 6 , as shown in Table 1).
[0096] Except for the special case of high interfacial potential difference at the hydrogen-vacancies interface causing corrosion of carbon supports, the carbon supports in the catalyst will preferentially undergo oxidative corrosion in the regions with low graphitization or defects during the electrochemical cycle. Fig.14 As shown, the corrosion sensitivity test of the carbon carrier in Example 5 shows that the O-KB300 carbon carrier oxidized by nitric acid pretreatment is most susceptible to corrosion, with a corrosion sensitivity value of 313.5%; the corrosion sensitivity values of N-KB300 and KB300 are 257.6% and 243.9%, respectively, which are very close, indicating that polyvinyl pyrrolidone, as a defect repairer on the surface of the carbon carrier, can effectively repair the defects caused by oxidation on the surface of the KB300 carrier, so that the corrosion resistance of the carbon carrier is restored to a certain extent, thereby improving the service life of the catalyst.
[0097] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogen fuel cell catalyst, characterized in that: The following steps are involved: Step S1, mixing crushed carbon black, polyvinyl pyrrolidone and a nitric acid solution with a concentration of 0.5 to 5M, heating to 60 to 120°C and reflux stirring for 3 to 12 hours, then rinsing the carbon black with deionized water until the filtrate after rinsing is neutral, then drying the rinsed carbon black at a drying temperature of 100 to 200°C under a vacuum environment for 6 to 12 hours to obtain pretreated conductive carbon black, and finally crushing the pretreated conductive carbon black to obtain a spare carbon carrier; wherein, when the carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed, the mass ratio of carbon black to polyvinyl pyrrolidone is 10 to 30:1, and the mass ratio of carbon black to nitric acid solution is 1:30 to 100; Step S2, dissolving platinum precursor powder and an auxiliary agent in a mixed solution of deionized water and an organic liquid, stirring the mixture for 0.5 to 1 h at a temperature of 80 to 100° C. and an ultrasonic power of not less than 2 kW to obtain a platinum precursor solution; wherein the mass ratio of deionized water to the organic liquid is 1:1 to 20, the mass ratio of the platinum precursor powder to the mixed solution is 1:20 to 200, and the mass ratio of the auxiliary agent to the mixed solution is 1:100-500; Step S3, placing the spare carbon carrier in the barrel, closing the barrel and evacuating the barrel so that the vacuum degree in the barrel is maintained at no more than 200pa, spraying the platinum precursor solution into the barrel, maintaining the barrel at a constant temperature of 20-25°C during the spraying period and continuously dispersing and stirring the material in the barrel, with a dispersion rate of 500-2000rpm and a dispersion stirring time of 10-60min; after the dispersion stirring, stop evacuating the barrel, and introduce nitrogen into the barrel to pressurize the material, with a pressurization pressure of 0.1-0.5MPa and a pressurization time of 5-20min; After the pressure treatment is completed, the barrel is evacuated again to keep the vacuum degree in the barrel not higher than 200 Pa and the barrel is kept at a constant temperature of 100° C. to evaporate the solvent for 1 to 2 hours; wherein, the mass ratio of platinum in the platinum precursor solution to the mass of the spare carbon carrier is 1:0.5 to 4, the platinum precursor solution is divided into no less than three parts, and one portion of the platinum precursor solution is sprayed during each spraying period. After the above-mentioned dispersion stirring, pressure treatment and solvent evaporation steps are completed, another portion of the platinum precursor solution is sprayed, and the above steps are repeated until all the platinum precursor solutions are sprayed to obtain the sample; Step S4, quenching the sample obtained in step S3 with liquid nitrogen and placing it in a freeze dryer for freeze drying for 8 to 24 hours to obtain a freeze-dried powder; Step S5, heat-treating the freeze-dried powder in a reducing mixed gas at a temperature of 400-900° C. for 1-3 hours to obtain a catalyst; wherein the reducing mixed gas includes 5-10 Vol% of reducing gas ammonia, and the rest is argon or nitrogen.
2. A method for preparing a hydrogen fuel cell catalyst according to claim 1, characterized in that: The carbon black added when the carbon black, polyvinyl pyrrolidone and nitric acid solution are mixed in step S1 has a specific surface area of 400 to 1200 m 2 / g, the added carbon black is carbon black that has been mechanically crushed and passed through a 400-mesh sieve, and the graphite crystallite size of the carbon black is 2-5nm.
3. A method for preparing a hydrogen fuel cell catalyst according to claim 1, characterized in that: The molecular weight of the polyvinyl pyrrolidone is not higher than 40,000.
4. The method for preparing a hydrogen fuel cell catalyst according to claim 1, characterized in that: The platinum precursor powder is any one of tetraamineplatinum dihydrogencarbonate, tetraamineplatinum oxalate, tetraamineplatinum hydrogenphosphate, tetraamineplatinum acetate, tetraamineplatinum sulfate, tetraamineplatinum nitrate, dinitrosodiammineplatinum, tetraamineplatinum dichloride, ammonium chloroplatinate, and tetraamineplatinum dihydroxide, or a combination of two or more thereof.
5. The method for preparing a hydrogen fuel cell catalyst according to claim 1, characterized in that: The auxiliary agent is any one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acyl alkanolamine polyoxyethylene ether and octylphenol polyoxyethylene ether.
6. A method for preparing a hydrogen fuel cell catalyst according to claim 1, characterized in that: The organic liquid is any one of isopropanol, n-propanol, glycerol, acetic acid, and trichloroacetaldehyde, or a combination of two or more thereof.
7. A hydrogen fuel cell catalyst, characterized in that: A catalyst prepared by the method for preparing a hydrogen fuel cell catalyst according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of platinum-carbon catalyst, platinum-carbon catalyst and catalyst coating film
CN115458755A
Preparation method of composite carbon carrier for loading platinum-based noble metal particles
CN116722160A
Nitrogen-doped carbon-supported platinum catalyst and preparation method thereof
CN118712405A
Method of preparing a mesoporous carbon composite material
US20210268481A1